Deformation Behavior of Grouted Sleeve Wall Connector Under Shear Load in Precast Process of Concrete Wall - Jen Hua Ling; Ahmad Baharuddin Abd. Rahman; Izni Syahrizal Ibrahim (Faculty of Engineering and Technology, Sampoerna University, 2022)
This study investigated the behaviour of grouted sleeve connectors under shear loads. Tapered Head Sleeve (THS) connectors were fabricated from mild steel pipes. Five test specimens and a control specimen were produced. Each test specimen comprised two walls, which were connected by THS. An incremental shear load was applied at the joint until the specimen failed. The behaviour of the specimens was analyzed based on the load-displacement response. The feasibility of THS as a wall connection was determined based on ductility ratio, failure mode, performance ratio, and serviceability ratio. THS required an embedded length of 8 times the bar diameter to generate sufficient bond strength. The specimens experienced bar dowel action, which led to a significant horizontal displacement with a ductility ratio of 27.5 to 55.9. The test specimens offered shear capacities comparable to the control specimen, with performance ratios close to 1.0. The service load was only 1/3 of the ultimate capacity, and thus THS was ineffective in resisting shear load. Shear keys would be required to strengthen the joint of the specimen.